HUMAN PAPILLOMAVIRUS IN THE ETIOLOGY OF HEAD AND NECK CARCINOMAS - Michl, Petr; Pazdera, Jindrich; Prochazka, Martin; Pink, Richard; Stosova, Tatana (Biomedical papers, 2010)
Background: For more than 20 years, infection with the human papillomavirus (HPV) has been of a matter of interest not only to gynecologists but also to maxillofacial surgeons and othorhinolaryngologists. HPV is generally known to be involved in cervical cancer. Recently, there are many clinical studies pointed out the potentially dangerous connection between HPV infection and head and neck carcinomas (HNC). HPV infection was identified as a possible etiological factor in 15-30% of HNC.Methods: Aim of this article is to summarize the recent knowledge about the HPV infection with regards to etiology of head and neck cancer.Results: It has been proven that HPV infection is related to development of head and neck cancer and that the sexual behavior has played an important role in the viral transmission. HNC of viral etiology have been observed mostly in younger people; their curability is difficult and prognosis serious.Conclusion: Beside the well known correlation between developing of new head and neck cancer and bad habits (smoking, alcohol abuse, poor oral hygiene etc.) we should take into consideration the sexual promiscuity and alternative sexual practices. Vaccination against cervical cancer, recommended to young women, should be extended to their male partners to prevent the virus transmission and decrease the HNC incidence.
Keywords: HPV infection/Head and neck carcinomas/Vaccination